Some (don’t) like it hot. The KlimaSeniorinnen v. Switzerland case before the European Court of Human Rights (to say nothing of the others) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The KlimaSeniorinnen v. Switzerland case (on climate change) was recently heard before the Grand Chamber of the European Court of Human Rights. This case sees an association of elderly women claiming the violation of their right to life and health by the Swiss State, which has failed to reduce CO2 emissions that cause global warming and the rise of temperatures, thus exposing elderly people to a greater risk of death. This case is certainly not an isolated one. The European Court, which up to now has been rather cautious in assessing environmental cases, is now faced with several important questions that could change its role in the European context. This paper, starting from the KlimaSeniorinnen case, aims to offer an overview of the climate litigation before the ECtHR, highlighting the main problematic issues.
Keywords: Global warming; climate change litigations; human rights; European Court of human rights; margin of appreciation